Reliability Express Control of the Gate Dielectric of Semiconductor Devices - V. A. Solodukha; G. G. Chigir; V. A. Pilipenko; V. A. Filipenya; V. A. Gorushko (Приборы и методы измерений, 2018)
The key element determining stability of the semiconductor devices is a gate dielectric. As its thickness reduces in the process of scaling the combined volume of factors determining its electrophysical properties increases. The purpose of this paper is development of the control express method of the error-free running time of the gate dielectric and study the influence of the rapid thermal treatment of the initial silicon wafers and gate dielectric on its reliability.The paper proposes a model for evaluation of the reliability indicators of the gate dielectrics as per the trial results of the test MDS-structures by means of applying of the ramp-increasing voltage on the gate up to the moment of the structure breakdown at various velocities of the voltage sweep with measurement of the IV-parameters. The proposed model makes it possible to realize the express method of the reliability evaluation of the thin dielectrics right in the production process of the integrated circuits.On the basis of this method study of the influence of the rapid thermal treatment of the initial silicon wafers of the KEF 4.5, KDB 12 wafers and formed on them by means of the pyrogenic oxidation of the gate dielectric for the error-free running time were performed. It is shown, that rapid thermal treatment of the initial silicon wafers with their subsequent oxidation results in increase of the error-free running time of the gate dielectric on average from 12.9 to 15.9 years (1.23 times greater). Thermal treatment of the initial silicon wafers and gate dielectric makes it possible to expand the error-free running time up to 25.2 years, i.e.1.89 times more, than in the standard process of the pyrogenic oxidation and 1.5 times more, than under application of the rapid thermal treatment of the initial silicon wafers only.